The Role of Advocates in Assisting the the accused of the Crime of Embezzlement of Complete Systematic Land Registration Fees (PTSL) - Muhammad Abu Aksan; Sri Kusriyah (Law Development Journal, 2020)
This study aims to determine the role of advocates in assisting defendants in complete systematic land registration fee embezzlement (PTSL), inhibiting factors. This research method uses an empirical juridical approach. The conclusion of this study is the role of advocates in assisting the accused of embezzling the complete systematic land registration fee (PTSL) at the Pati District Court, Decision Number: 13 / Pid.B / 2020 / Pn Pti, with the defendant I Subronto, S.Pd . Bin Ngaseri, Defendant II Muh. Gufron Bin Ahmadi, therefore, was sentenced to imprisonment for 6 (six) months each while defendant III Muhlisin Bin Matruri was sentenced to imprisonment of 5 (five) months. Inhibiting factors The role of advocates in assisting the accused of embezzling the complete systematic land registration fee (PTSL) at the Pati District Court, the number of witnesses presented by the Public Prosecutor in the trial was the Village Government of Alasdowo, Kec. Dukuhseti Kab.Pati who is involved in the PTSL Program, but in giving their testimony regarding the use of the PTSL application fee they seem not to know by covering up the real facts, There are no regulations governing the PTSL program in Alasdowo Village, Kec. Dukuhseti Kab. Pati, so it was difficult to present Expert Witnesses.Keywords: Legal Counsel, embezzlement, Defendant.